2020
DOI: 10.3390/jcm9061912
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Efficacy of the Workshop Vs. Online SUCCEAT (Supporting Carers of Children and Adolescents with Eating Disorders) Intervention for Parents: A Quasi-Randomised Feasibility Trial

Abstract: Interventions for main carers of adult patients with anorexia nervosa (AN) can reduce the caregiving burden and increase caregiver skills. However, the effectiveness and feasibility for carers of adolescent patients, the optimal form of the intervention and long-term outcomes are largely unknown. We evaluated the efficacy and feasibility of the “Supporting Carers of Children and Adolescents with Eating Disorders in Austria” (SUCCEAT) workshop vs. online intervention. Main caregivers (parents) of adolescent pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
45
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(50 citation statements)
references
References 37 publications
4
45
0
1
Order By: Relevance
“…However, there were no systematic differences between the WS and ONL groups at the baseline. Details on the randomization procedure are reported elsewhere [26].…”
Section: Recruitment and Randomisationmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there were no systematic differences between the WS and ONL groups at the baseline. Details on the randomization procedure are reported elsewhere [26].…”
Section: Recruitment and Randomisationmentioning
confidence: 99%
“…Caregivers received weekly handouts, a manual to read more about the topics addressed [30], and a DVD [31] with case examples of unhelpful and helpful communication. A detailed description of the interventions is provided by Franta et al [28] and Truttmann, Philipp et al [26].…”
Section: Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Philipp et al [ 27 ] demonstrated that parental expressed emotion (associated with higher distress and a lack of skills) was reduced after interventions for caregivers (namely the SUCCEAT program), and that this reduction positively influenced patients’ outcomes. Likewise, the results from the study of Truttmann et al [ 26 ] provide support for the efficacy of the same interventions for caregivers (i.e., SUCCEAT) reducing parental burden, distress and psychopathology. Last but not least, Treasure et al [ 23 ] reviewed the underpinnings of the Cognitive Interpersonal Model for AN and how this can be targeted to treatment.…”
mentioning
confidence: 90%
“…To address this important health issue, the current Special Issue collected 21 articles examining the most recent and relevant scientific findings regarding advances in ED. The published articles comprised three reviews and 18 research articles focusing on different aspects, such as genetic [ 7 ] and epigenetic factors [ 8 ], biomarkers [ 9 ], comorbidity [ 10 , 11 , 12 , 13 , 14 ], clinical phenotypes [ 15 , 16 ], neurocognition [ 12 , 17 , 18 , 19 , 20 , 21 ], treatment predictors [ 22 ], and treatment models and therapeutic targets [ 19 , 23 , 24 , 25 , 26 , 27 ]. Altogether, these studies may provide increased knowledge about the pathogenesis, the risk factors, the maintenance factors, and the most appropriate treatments tools for ED.…”
mentioning
confidence: 99%